Responding to literature texts through films in English and the L1 within a multiliteracies pedagogy - Rajendram, Shakina; Govindarajoo, Mallika V. (Australian International Academic Centre, 2016)
This article presents the results of a study exploring the aesthetic and critical responses of English as a Second Language (ESL) learners when engaging in the multimodal design of literature texts through films in English and their first language (L1). Participants consisted of 25 culturally and linguistically heterogeneous first-year undergraduate students in a Literature in English Language Teaching program in a Malaysian public university. The participants engaged in a multi-modal design of the novel Step by Wicked Step by Anne Fine in three phases over a period of eight weeks based on the four components of the multiliteracies approach: situated practice, overt instruction, critical framing, and transformed practice. The transformed practice component of this approach involved students making and presenting short films both in English and in a local Malaysian language or dialect. Data for the study came from six focal participants’ journal reflections throughout the project and semi-structured interviews with them. The findings showed that the multimodal design of texts through films in the L1 increased personal meaningfulness and intercultural understanding. It also allowed learners to function as language experts, take liberties with the text, and look beyond the text for inspiration from dramas and movies.